2012
DOI: 10.1091/mbc.e12-01-0034
|View full text |Cite
|
Sign up to set email alerts
|

cis-Golgi proteins accumulate near the ER exit sites and act as the scaffold for Golgi regeneration after brefeldin A treatment in tobacco BY-2 cells

Abstract: Particular cis-Golgi proteins accumulate in novel punctate structures close to ERES by BFA treatment in tobacco BY-2 cells. These structures reassemble first to form cis-Golgi after BFA removal, and the Golgi stacks regenerate in the cis-to-trans order. This indicates that the punctate structures act as the scaffold for Golgi regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 69 publications
(112 reference statements)
5
95
0
Order By: Relevance
“…1E). The observation on the association of AtSar1a punctate with the Golgi apparatus is consistent with previous studies using superresolution microscopy that showed that ERES are surrounded by the Golgi apparatus and that ERES shows more numbers than the Golgi (15,23). In contrast, most of the AtSar1c-GFP-labeled punctae were not Golgi-associated under superresolution microscopy.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…1E). The observation on the association of AtSar1a punctate with the Golgi apparatus is consistent with previous studies using superresolution microscopy that showed that ERES are surrounded by the Golgi apparatus and that ERES shows more numbers than the Golgi (15,23). In contrast, most of the AtSar1c-GFP-labeled punctae were not Golgi-associated under superresolution microscopy.…”
Section: Resultssupporting
confidence: 91%
“…In mammals, ERES are frequently associated with the ER-Golgi intermediate compartment (ERGIC). The presence of ERGIC in higher plant cells remains elusive but a recent study suggests that the SYP31 compartment may represent a scaffold to build the Golgi stack, similar to the ERGIC in mammals (15). COPII components have been used as markers to study ERES in plants with various working models on the spatial relationship between ERES and Golgi (16).…”
Section: Resultsmentioning
confidence: 99%
“…Golgi stacks in tobacco cells are formed in the order from cis-to trans-cisternae and that the presence of scaffold at cis-most side, which we named Golgi entry core compartment (GECCO), plays a role of receiving cargo from the ER (Ito et al, 2012(Ito et al, , 2017. Furthermore, computational simulation has implicated self-organizing properties of Golgi cisternae during reassembly processes (Tachikawa and Mochizuki, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate the anomalies of the Golgi morphology, the arrangement of cis and trans cisternae in Golgi stacks was examined in the wild-type and #46-3 plants stably expressing ST-mRFP, a trans-Golgi marker (sialyl transferase from rat) (Boevink et al, 1998;Ito et al, 2012;, in addition to ERD2-GFP. As shown in Fig.…”
Section: Localization Analysis Of Cis-and Trans-golgi In the #46-3 Mumentioning
confidence: 99%
“…However, with improved resolution, it looks more likely that small structures containing a cis-Golgi marker move around and grow over time before entering the maturation phase. We usually use Suppressor of Erd2 Deletion (Sed5; the counterpart of SYP31/SYP32 of plants and syntaxin5 of mammals) as a cis-Golgi marker, but considering the findings we have made in tobacco BY2 cells (Ito et al, 2012), the yeast Sed5 compartment may represent both a sorting platform like the ERGIC as well as the first enzymatic station of the glycosylation factory (see also below). (5) Is a hug-andkiss mechanism specific to yeast?…”
Section: Akihiko Nakano: a Common Mechanism For Er-to-golgi Traffic: mentioning
confidence: 99%